1989
DOI: 10.1111/j.1574-6968.1989.tb03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly-β-hydroxybutyric acid in staphylococci

Abstract: Poly‐β‐hydroxybutyric acid (PHB) was extracted from various species of staphylococci isolated from different sources. IR and UV spectrophotometry and NMR analysis revealed that the compound consisted only of the β‐hydroxybutyrate. The PHB level in the richest strain among investigated staphylococci is about 64‐fold less than in bacilli. The intrinsic viscosity number of this polymer is more than twice greater in the case of the staphylococcal product than that of bacilli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Staphylococcus P(3HB) has been extracted from various species of Staphylococci such as Staphylococcus aureus, Staphylococcus xylosus, Staphylococcus simulans, Staphylococcus warneri, Staphylococcus epidermidis and Staphylococcus haemolyticus (Szewczyk and Mikucki 1989). P(3HB) is present in cells in trace quantities (such as 0.15% w/w dcw for S. aureus grown in fructose) and most importantly it does not form granules as in other bacteria indicating possible existence as cPHB.…”
Section: Rhodococcusmentioning
confidence: 99%
See 2 more Smart Citations
“…Staphylococcus P(3HB) has been extracted from various species of Staphylococci such as Staphylococcus aureus, Staphylococcus xylosus, Staphylococcus simulans, Staphylococcus warneri, Staphylococcus epidermidis and Staphylococcus haemolyticus (Szewczyk and Mikucki 1989). P(3HB) is present in cells in trace quantities (such as 0.15% w/w dcw for S. aureus grown in fructose) and most importantly it does not form granules as in other bacteria indicating possible existence as cPHB.…”
Section: Rhodococcusmentioning
confidence: 99%
“…P(3HB) is present in cells in trace quantities (such as 0.15% w/w dcw for S. aureus grown in fructose) and most importantly it does not form granules as in other bacteria indicating possible existence as cPHB. However, the metabolic roles of PHAs in this genus is poorly understood (Szewczyk 1992).…”
Section: Rhodococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Already in formerly published studies, detection of intracellular polysac-* Dedicated to Prof. Dr charides [13,14], poly-P-hydroxybutyric acid (PHB) granules [15], and endospores [16] was reported by authors using dispersive infrared spectroscopy. More recently, after the advent of modem and computerised Fourier-Transform IR spectroscopy some authors reported more details about PHB extracted from staphylococci [17] and exopolymer in Pseudomonas atlantica [18]. In the latter study difference spectra and band ratios for analysis of cell components of powdered bacteria were given for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…PHB occurred only in some of the investigated strains. In 1989 we published work which proved that PHB is accumulated by all staphylococci but in changing and small, sometimes trace, amounts [10]. Large batches of staphylococci isolated from different sources were grown on Nutrient Broth enriched with 1% glucose.…”
Section: Occurrence Of Phb In Staphylo-coccimentioning
confidence: 99%